Single layer of nickel hydroxide nanoparticles covered on a porous Ni foam and its application for highly sensitive non-enzymatic glucose sensor - Kung, Chung-Wei; Cheng, Yu-Heng; Ho, Kuo-Chuan (Sensors and actuators. B, Chemical, 2014)
•Commercial Ni foam is applied for a cyclic electrochemical treatment.•Single layer of Ni(OH)2 nanoparticles (NP) covers the full surface of the Ni foam.•The Ni(OH)2 NP/Ni foam electrode is applied for non-enzymatic glucose detection.•A high sensitivity of 1950.3μA/mM-cm2 can be achieved.•The sensor shows a linear range up to 6.0mM and a detection limit of 0.16μM. A single layer of nickel hydroxide nanoparticles (Ni(OH)2 NPs) was covered on the full surface of a porous Ni foam by simply applying an electrochemical cyclic voltammetric (CV) treatment on a bare Ni foam substrate for 100 cycles in 1.0M NaOH solution. The surface morphology of the obtained Ni(OH)2 NPs/Ni foam electrode was examined by scanning electron microscopy. The thickness of the Ni(OH)2 NPs layer on the electrode was estimated by X-ray photoelectron spectroscopy with Ar+ ion etching. In CV measurement, the Ni(OH)2 NPs/Ni foam electrode exhibited excellent electrocatalytic ability toward glucose in NaOH solution. The Ni(OH)2 NPs/Ni foam electrode was successfully used for the quantification of glucose by an amperometric method. The sensing parameters include a high sensitivity of 1950.3μA/mM-cm2, a linear range from 0.6 to 6.0mM, a detection limit of 0.16μM, and an applied potential of 0.45V (vs. Ag/AgCl/KCl sat’d). The excellent performances obtained in the interference test, the long-term durability test in atmosphere, and the reproducibility test of the Ni(OH)2 NPs/Ni foam sensor indicate the applicability of the proposed electrode as a reliable non-enzymatic glucose sensor.